2015
DOI: 10.1016/j.jhsa.2015.06.117
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 1-Ethyl-3-(3-Dimethylaminopropyl) Carbodiimide Suture Coating on Tendon Repair Strength and Cell Viability in a Canine Model

Abstract: Purpose To determine if impregnating a suture with a cross-linking agent, f 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC), improved suture pull-out strength and cell viability. Methods Canine flexor digitorum profundus tendons were cut in canine zone D, and a single suture loop was placed in each end, with sutures soaked in either saline or in an EDC solution with a concentration of 1%, 10%, or 50%. Suture pull-out strength, stiffness, and elongation to failure was determined by pulling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Comparing the leaching liquor from water annealed SF film, the leaching liquor from GSH-modified SF film decreased the HEK293 cell viability slightly. This difference perhaps to be relative with the presence of EDC trace residue within the sample, and the previous study demonstrated that EDC had negative effects on the cell viability [34]. Apart from that, both water annealed and GSH-modified SF films exhibited high biocompatibility as their cell viabilities were higher than 100% relative to control.…”
Section: Resultsmentioning
confidence: 89%
“…Comparing the leaching liquor from water annealed SF film, the leaching liquor from GSH-modified SF film decreased the HEK293 cell viability slightly. This difference perhaps to be relative with the presence of EDC trace residue within the sample, and the previous study demonstrated that EDC had negative effects on the cell viability [34]. Apart from that, both water annealed and GSH-modified SF films exhibited high biocompatibility as their cell viabilities were higher than 100% relative to control.…”
Section: Resultsmentioning
confidence: 89%
“…Adoption of this technology by surgeons would be facilitated by the fact that it would not modify current clinical suture techniques. In a similar study by Thoreson et al the authors used 1‐Ethyl‐3‐(3‐Dimethylaminopropyl) Carbodiimide (EDC) as the crosslinking agent, in contrast to the nontoxic cross linking agent, genipin (GP) used in the present study. Notably, the repair stiffness and repair strength obtained by the genipin‐loaded sutures were significantly higher compared to the EDC study results.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study by Thoreson evaluated for their loading efficiency, release profiles, and mechanical properties. The crosslinking agent GP was used in this study due to its beneficial effect on connective tissues, 30,37,38 well-studied pharmacological properties, 53,54 its low toxicity compared to other crosslinking agents, 55,56 and our prior experience with this specific agent. 30 PGA was chosen for the suture material because it is one of the most common clinically used suture materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Experimental crosslinking agents coating sutures, including 1-ethyl-3-(3-dimethylaminopropyl) carbo-diimide hydrochloride (EDC) and cyanoacrylate, also increase suture-tendon interactions and crosslink the tendon tissue immediately adjacent to the suture. 43,44 These mechanical approaches offer an opportunity to improve repair strength, but do not inherently decrease adhesions or enhance the healing process.…”
Section: Introductionmentioning
confidence: 99%